Cutaneous hypersensitivity reactions due to thiacetazone in the treatment of tuberculosis in Zambian children infected with HIV-I. Issue 5 (May 1993) - Chintu, C; Luo, C; Bhat, G; Raviglione, M; DuPont, H; Zumla, A
Abstract : Tuberculosis is one of the most common infections in Zambian adults and children infected with HIV. In Africa, cutaneous hypersensitivity reactions attributed to thiacetazone during treatment of tuberculosis in adults infected with HIV-I have been well documented. This study monitored adverse drug reactions during treatment for tuberculosis over an 18 month period (1 April 1990 to 31 October 1991) in 237 children with a clinical diagnosis of tuberculosis (125 boys and 112 girls; 88/237 (37%) infected with HIV-I) and 242 control children (149 boys and 93 girls; 26/242 (11%) infected with HIV-I). Twenty two (9%) of the 237 children with tuberculosis developed hypersensitivity skin reactions during the course of treatment. Adverse skin reactions were seen more often in children infected with HIV than in those who were not (odds ratio 11.65, 95% confidence interval 3.07 to 34.88). These represented 19 (21%) of 88 children infected with HIV and three (2%) of 149 children not infected with HIV. These skin reactions occurred after a period of treatment ranging between two and four weeks among 14 children receiving the HST (isoniazid, streptomycin, thiacetazone) regimen and eight children receiving the HSTR (isoniazid, streptomycin, thiacetazone, rifampicin) regimen. Twelve (55%) of the 22 children who reacted adversely to treatment developed the Stevens-Johnson syndrome. All 12 of these children with the Stevens-Johnson syndrome were infected with HIV. The mortality among these children who developed the Stevens-Johnson syndrome was 91% (11 of 12 died within three days of the onset of the reaction). No further reactions were observed in the 11 children who recovered from the cutaneous hypersensitivity reactions after thiacetazone was discontinued over a period of six months of further treatment of tuberculosis. The results of this study were in part responsible for the recommendations put forward by the World Health Organization to avoid the use of thiacetazone in the treatment of tuberculosis in children infected with HIV.